Genetic instability-related lncRNAs predict prognosis and influence the immune microenvironment in breast cancer - Lv, Zhenyi; Wang, Qiang; Liu, Xuxu; Du, Zhiwei; Liang, Wenping; Liu, Tianming; Zheng, Yi; Ma, Biao; Xue, Dongbo (Frontiers in Genetics, 2022)
Genome instability is a hallmark of cancer, and the function of lncRNAs in regulating genomic stability has been gradually characterized. However, the prognostic value of lncRNAs related to genetic instability has not been found in breast cancer. Here we constructed a genetic instability-related lncRNA model including U62317.4, SEMA3B-AS1, MAPT-AS1, AC115837.2, LINC01269, AL645608.7, and GACAT2. This model can evaluate the risk and predict the survival outcomes of patients. Further analysis showed that the differentially expressed genes between the high- and low-risk groups were enriched in immunity and cornified envelope formation pathways. In addition, M2 macrophages infiltrated more obviously in the high-risk group. In summary, lncRNAs related to genetic instability may influence the development of breast cancer through immune infiltration and keratinization. This study provides a wider insight into breast cancer development and treatment.